1995
DOI: 10.1007/978-1-4899-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination and Task Avoidance

Abstract: and Associates with a Foreword by Norman A. Milgram Discusses the historical origins, definition, and measurement of procrastination, as well as exploring its relationship with academic tasks, agitation, perfectionism, depression, passiveaggression, and obsessions-compulsions. Features previously unpublished data from the pioneering studies of Lay, Flett, Hewitt, and Schouwenburg. A volume in the Plenum Series in Social/Clinical Psychology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
145
1
112

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 424 publications
(269 citation statements)
references
References 0 publications
11
145
1
112
Order By: Relevance
“…Across cultural and sex groups, the scale was reliable at alpha levels from .80 to .90, consistent with past work (Frost & Gross, 1993;Frost & Shows, 1993;Gayton et al, 1994). The results provide further evidence for the inter-item reliability of this scale for American men and women, and new evidence for Chinese men and women.…”
Section: Scale Reliability Summarysupporting
confidence: 84%
See 3 more Smart Citations
“…Across cultural and sex groups, the scale was reliable at alpha levels from .80 to .90, consistent with past work (Frost & Gross, 1993;Frost & Shows, 1993;Gayton et al, 1994). The results provide further evidence for the inter-item reliability of this scale for American men and women, and new evidence for Chinese men and women.…”
Section: Scale Reliability Summarysupporting
confidence: 84%
“…This construct has received considerable research attention (Ferrari, Johnson, & McCown, 1995), and has been found to predict many resource-intensive decision tendencies in the general population. Individuals high on indecisiveness take more time to choose among alternatives (Frost & Shows, 1993), use less-exhaustive decision strategies (Ferrari & Dovidio, 2000, require greater cognitive effort to make decisions (Ferrari & Dovidio, 2001), are more threatened by ambiguous situations (Rassin & Muris, 2005b), and are more likely to postpone decisions (Rassin & Muris, 2005a), compared to those low on indecisiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in addition to the already mentioned sunk cost fallacy (Ross and Staw, 1993) and escalation of commitment (Staw, 1981), there are numerous other behavioral phenomena that might influence the intuitive choice of a disinvestment trigger towards postponement of this irreversible decision such as status-quo bias (Samuelson and Zeckhauser, 1988;Kahneman et al, 1991), resistance to change (Grabitz, 1971), inaction inertia (Tykocinski and Pitman, 1998), inaction or omission bias (Ritov and Baron, 1992), decision avoidance (Anderson, 2003), and procrastination (O'Donogue and Rabin, 1999;2001;Ferrari et al, 1995 In the present study, we call this behavior 'psychological inertia' to contrast this type of inertia with the 'options-based' type of inertia postulated in Propositions 1-3.…”
Section: Behavioral Hypothesesmentioning
confidence: 99%